2020
DOI: 10.1144/jgs2019-157
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a salt-rich transtensional rifted margin, eastern North Pyrenees, France

Abstract: In this field study we reinterpret the narrow eastern North Pyrenean Zone, France, as an inverted salt-rich transtensional rift system based on identification of halokinetic depositional sequences across rift platform to distal rift margin domains with a cumulative throw of >2.8 km on steep Cretaceous faults. The rift platform records extension on detached rotational faults above Triassic evaporites from Jurassic to Aptian with uplift and erosion during the Albian. Transtensional Aptian–Albian minibasins al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 125 publications
(193 reference statements)
6
42
0
Order By: Relevance
“…An increasing volume of work documents the mobilization of Keuper evaporites from early Jurassic and throughout the Alpine cycle in and around western Mediterranean orogenic belts (e.g. Graham et al 2012;Espurt et al 2018Espurt et al , 2019aLabaume & Teixell 2019;Vergès et al 2020;Célini et al 2020;Vergés et al 2020;Ford & Vergés 2021). The Corbières-Languedoc Transfer Zone has long been recognized as an area with significant volumes of Keuper evaporites at surface and at depth (Berger et al, 1982;Berger et al, 1997;Berger et al, 1993;Ellenberger et al, 1987;Lespinasse et al, 1982).…”
Section: Evidence Of a Jurassic Decoupled Extensionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing volume of work documents the mobilization of Keuper evaporites from early Jurassic and throughout the Alpine cycle in and around western Mediterranean orogenic belts (e.g. Graham et al 2012;Espurt et al 2018Espurt et al , 2019aLabaume & Teixell 2019;Vergès et al 2020;Célini et al 2020;Vergés et al 2020;Ford & Vergés 2021). The Corbières-Languedoc Transfer Zone has long been recognized as an area with significant volumes of Keuper evaporites at surface and at depth (Berger et al, 1982;Berger et al, 1997;Berger et al, 1993;Ellenberger et al, 1987;Lespinasse et al, 1982).…”
Section: Evidence Of a Jurassic Decoupled Extensionmentioning
confidence: 99%
“…2a) bears witness to the presence of diapirs that pierced to the surface. Ford et Vergés (2021) have recently documented salt-controlled depocentres, particularly of Early Cretaceous age, in the easternmost North Pyrenean Zone.…”
Section: Evidence Of a Jurassic Decoupled Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The orogenic shortening was accommodated in the upper crust by reactivation of the inherited Cretaceous extensional faults, as thrust faults (Debroas, 1990), while the middle crust and exhumed mantle were subducted beneath the European crust (Teixell et al, 2016(Teixell et al, , 2018. The orogen extended eastwards (Ford and Vergés, 2020), in Corbières (Viallard, 1987;Lamotte et al, 2002), Languedoc (Arthaud and Laurent, 1995) and southern Provence (Lacombe and Jolivet, 2005;Bestani et al, 2015), across the present-day Gulf of Lion Gorini et al, 1994). It was later dismantled in Oligocene time to give way to the Gulf of Lion rifted margin Gorini et al, 1994;Séranne et al, 1995;Mauffret and Gorini, 1996;Mascle and Vially, 1999;Séranne, 1999;Guennoc et al, 2000;Lacombe and Jolivet, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the last decade emphasised the global geodynamic models of the extension, particularly the rise of the mantle, followed by the Cenozoic compression due to plate movements, and contributed first to putting salt tectonics in the background. Recent works tend, however, to reconsider the role of salt as significant in the local deformation mechanisms at the interfaces between basement rocks and the pile of sedimentary formations in the Mesozoic basins and to propose mixed models (Duretz et al, 2020;Ford and Verges, 2020) as already suggested by Jammes et al (2009). Pre-rift salt controls the Cretaceous smooth-slopes extensional basins and the subsequent continental rifting mode (Lagabrielle et al 2020).…”
mentioning
confidence: 99%